DECARBONIZATION OF THE ECONOMY: THE ESSENCE AND MECHANISMS FOR ITS IMPLEMENTATION - Abdikarimova Aynura Abay qizi (American Journals, 2024)
This article covers the essence of decarbonization of the economy and the mechanisms of its implementation. The purpose of decarbonization is to replace fossil fuel-based systems with electricity generated using low carbon sources such as renewable energy sources.
Keywords: Carbonization, greenhouse gas emissions, renewable energy sources, Paris Agreement, global climate crisis, green economic recovery, greenhouse gases.